(untitled) - Loksova, Zuzana (Doprava a spoje, 2008)
This paper deals with public transport coordination which is the basic condition of integrated transport system. The article includes some sequence of steps for removal limitations in legislative and conceptional providing of concordance the principles of transport politics with integration conditions of public transport services